E-learning adoption in the classroom: implementation strategy, effectiveness and challenges - Nasikin, Mohd Farid; Kamarudin, Nurzatulshima; Mustakim, Siti Salina; Khalid, Asma Nazifa; Abd Halim, Hamizah; Roslan, Nur Ayuni Aini (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Towards the development of 21st century teaching and learning, exist variation of teaching methods adapted in the classroom instruction. All these are to ensure learners' interest and participation in the teaching and learning keeps on going interactively. Electronic teaching is one of the popular methods that have been carried out by teachers, known as e-learning. This paper discusses the provision of new experience in the process of teaching and learning to both teachers and students. The focus on the implementation strategies of e-learning, its effectiveness for students, and limitation encountered in its implementation are highlighted too.